PENGEMBANGAN APLIKASI “PETASAH” BERBASIS WEB UNTUK PENGELOLAAN ASET SEKOLAH DI SMA NEGERI 1 KELAPA KAMPIT - Irsyad Akbar (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This research aims to develop a web-based application, "Petasah", designed to improve the efficiency and effectiveness of asset management at SMA Negeri 1 Kelapa Kampit. The previous asset management system, which still relied on manual methods, was considered inefficient due to challenges such as data entry errors, slow asset tracking, and time-consuming reporting. The application utilizes QR Code technology for real-time asset tracking, facilitating asset recording and status monitoring. Through testing and evaluation, the "Petasah" application was found to enhance speed, accuracy, and transparency in asset management. The study also identified the need to integrate the application with other systems, such as the school’s financial system, to increase overall efficiency. The implementation of this application is expected to be applied in other schools, providing an efficient solution for asset management and facilitating faster, data-driven decision-making.